Pengaruh Intervensi Sleep Hygiene terhadap Kualitas Tidur pada Pasien Congestive Heart Failure : Suatu Literatur Sistematis - Nita Kardilah (Yayasan Literasi Sains Indonesia, 2025)
Congestive Heart Failure occurs when cardiac contractility is reduced and the ventricles are unable to pump out as much blood as they enter during diastole. Patients with Congestive Heart Failure (CHF) need adequate sleep because of good sleep quality will improve heart muscle cells. Sleep Hygiene is a behavioral practice based on our knowledge of sleep physiology and pharmacology, which has been shown to improve sleep quality (Jefferson et al, 2005). Sleep quality can be measured by PSQI with the final result ≤ 5 (Good) and 5-21 (Poor). This literature review aims to find evidence of sleep quality in heart failure patients and their management. Methods : Literature study from some a journals sourced from Google Scholar, with the keywords Sleep Hygiene and Congestive Heart Failure, as many as 17 journals were selected for review. Results: Application of Sleep Hygiene showed a change in sleep patterns and sleep quality in Congestive Heart Failure (CHF) patients. Discussions : The result is sleep deprivation in people with heart failure that affects their quality of life, tends to suffer from depression which results in increased death and ventricular arrhythmias. Handling in the form of pharmacological and non pharmacological therapy. Implications for nursing science of sleep quality problems of heart failure patients are sought to develop a model of non-pharmacological regimen therapy, taking into account psychosocial and spiritual aspects.